Momentum or contrarian investment strategies: Evidence from Dutch institutional investors - de Haan, Leo; Kakes, Jan (Journal of Banking & Finance, 2011)
This paper analyses investment strategies of three types of Dutch institutional investors – pension funds, life insurers and non-life insurers – over the period 1999–2005. We use balance sheet and cash flow data, including purchases and sales of equity, fixed income and real estate. We trace asset reallocations back to both active trading and revaluations and link investment decisions to firm-specific characteristics and macroeconomic variables. Overall, our results indicate that all three investor types tend to be contrarian traders, i.e. they buy past losers and sell past winners. Especially pension funds showed this behaviour in the most turbulent part of the sample – the crash of 2002 and early 2003 – implying that these institutions have a stabilising impact on financial markets when this is needed most. Life insurers tend to be contrarian traders when they have a high proportion of unit-linked policies, while non-life insurers are contrarian when they have a more risky business model.